Value orientations of adolescents and the five‑factor personality model - Radovanovic, Ivana D.; Radovanović, Dobrivoje (Sociološki pregled, 2025)
The subject of this research is to determine whether and to what extent the traits of the Five-Factor Model of personality influence the acceptance or rejection of value orientations: Hedonism, Utilitarianism, Activism, and Altruism. The sample consisted of 832 adolescents –high school students in Belgrade, aged between 15 and 19. Personality data were collected using the NEO FFI test, standardized for use in Serbia. Value orientations were assessed using a modified version of the basic questionnaire model from previous studies. The data were collected during 2018. The relationships between personality traits and value orientations were analyzed using the canonical correlation analysis. In the subsample of boys, four pairs of significant canonical factors were identified. The first pair had a canonical correlation of .372, while the remaining three were considerably lower. In this most important first pair, low Agreeableness and low Conscientiousness significantly influenced the acceptance of Hedonism and the rejection of Utilitarianism and Altruism. In the subsample of girls, the first pair of canonical factors had a correlation of .426. In this relationship, high Neuroticism and high Agreeableness had a significant influence on the strong rejection of Hedonism and a notable acceptance of the Utilitarian value orientation.
Keywords: adolescents; personality traits; value orientations